OSTEORADIONEKROSIS PASCA EKSTRAKSI GIGI PASIEN DENGAN RIWAYAT KANKER NASOFARING - Yayun Siti Rochmah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Osteoradionecrosis (ORN) post dental extraction is post dentalextraction complication with post radiation cancer theraphy. Objective : to present rare case, ORN post dental extraction with post radiation Ca nasopharing therapy 3 years ago.Case Management: A 54 years old patient reported to the dental out-patient department with a chief complaint of pus discharge from right buccal since post dental extraction 6 months ago. He gave a history of a nasopharing Carcinoma with histopatology as squamous cell carcinoms 3 years ago and radio therapy but no surgery. Intraoral examination, exposed necrotic bone found from right lower retromolar area 46 with pus discharge. Radiographic view was likely squester. Local surgical debridement and the sequestrectomy was undertaken with general anaesthesia. Antibiotic injection treatment was ceftriaxon 2x 1gram, infus metronidazol 3x500 mg and ketorolac 3x1 ampul, the patient was treated for 3 days and educated to maintain his oral hygiene with povidone iodine gargle.Discussion: Osteoradionecrosis (ORN) is late effect of radiation therapy thatresults in irreversible tissue death, which is clinically observed as bony exposure for more than 3 months duration. The mandible is affected more often than the maxilla or any other bones of head and neck region. The incidence of ORN in the mandible is reported to be between 2% and 22% and most often affects the body of the mandible. Ideal time is one year minimal post radiotherapy to get maximal vascularization for optimal healing. But immunity factor and radiation doses can trigger emergense ORN.Conclusion: Need time consideration, clinic analysis and pathologys before doing dental extraction for post radiotherapy cancer cases to prevent ORN.